1975
DOI: 10.1128/jb.121.2.664-669.1975
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial ribosomes in barotolerance

Abstract: The effects of high hydrostatic pressures on protein synthesis by whole cells and cell free preparations of Escherichia coli, Pseudomonas fluorescens, and Pseudomonas bathycetes were determined. Actively growing cells of P. bathycetes and P. fluorescens were less sensitive than were E. coli cells. Protein synthesis by cell free preparations of E. coli and P. fluorescens showed the same extent of inhibition as their respective whole cell preparations, whereas cell free preparations of P. bathycetes showed a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 11 publications
5
30
0
Order By: Relevance
“…Early studies in bacteria [Landau, 1966, 1967; Pope et al, 1975a,b] and eukaryotic cells [Scheck and Landau, 1982a,b] have shown that high hydrostatic pressure inhibits the protein synthesis. The activity of rat ribosomes decreased with the increase of the applied pressure, so that total inhibition was reached at 240 MPa [Lu et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in bacteria [Landau, 1966, 1967; Pope et al, 1975a,b] and eukaryotic cells [Scheck and Landau, 1982a,b] have shown that high hydrostatic pressure inhibits the protein synthesis. The activity of rat ribosomes decreased with the increase of the applied pressure, so that total inhibition was reached at 240 MPa [Lu et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of both a barosensitive E. coli system and a barotolerant P. fluorescens system thus allowed for a series of experiments involving interchanges of ribosomes and supernatant factors in polyuridylate [poly(U)]-directed, polyphenylalaninesynthesizing preparations. Such experiments showed clearly that barotolerance in P. fluorescens was associated with the ribosomes rather than the soluble components of the system (13). Additional manipulation of the 50S and 30S ribosomal subunits in interchange experiments revealed that resistance to inhibition by pressure was associated with the 30S ribosomal subunit of P. fluorescens (18).…”
mentioning
confidence: 99%
“…Growth conditions. Maintenance and growth conditions for each organism were essentially those which have been described in a previous publication (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations